2006
DOI: 10.2174/157015906778520773
|View full text |Cite
|
Sign up to set email alerts
|

Neurochemistry of the Nucleus Accumbens and its Relevance to Depression and Antidepressant Action in Rodents

Abstract: There is accumulating evidence that the nucleus accumbens (NAc) plays an important role in the pathophysiology of depression. Given that clinical depression is marked by anhedonia (diminished interest or pleasure), dysfunction of the brain reward pathway has been suggested as contributing to the pathophysiology of depression.Since the NAc is the center of reward and learning, it is hypothesized that anhedonia might be produced by hampering the function of the NAc. Indeed, it has been reported that stress, drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
113
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 193 publications
(122 citation statements)
references
References 167 publications
(229 reference statements)
7
113
0
2
Order By: Relevance
“…: Rogge et al, 2008;Shirayama and Chaki, 2006). More specifically, in a Korean population, association was found between a polymorphism in intron 1 of the CART gene and alcoholism (Jung et al, 2004), and CART-peptide containing neurons are activated by acute administration of psychostimulants (Rogge et al, 2008;Shirayama and Chaki, 2006). Sex-specificity has been consistently found in stress adaptation and stress-induced brain diseases (Afifi, 2007;Kessler et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…: Rogge et al, 2008;Shirayama and Chaki, 2006). More specifically, in a Korean population, association was found between a polymorphism in intron 1 of the CART gene and alcoholism (Jung et al, 2004), and CART-peptide containing neurons are activated by acute administration of psychostimulants (Rogge et al, 2008;Shirayama and Chaki, 2006). Sex-specificity has been consistently found in stress adaptation and stress-induced brain diseases (Afifi, 2007;Kessler et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…There is substantial evidence connecting CART with reward circuitries in the mammalian brain (for review see e.g. : Rogge et al, 2008;Shirayama and Chaki, 2006). More specifically, in a Korean population, association was found between a polymorphism in intron 1 of the CART gene and alcoholism (Jung et al, 2004), and CART-peptide containing neurons are activated by acute administration of psychostimulants (Rogge et al, 2008;Shirayama and Chaki, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…However, these medicines actually have no antidepressant effect. 44) To avoid false positives in the following test, normal mice were exposed to the open-field apparatus for 5 min. The results showed that AST did not increase or reduce locomotor activity of normal mice, indicating that AST does not produce neural excitability.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic smoking has been shown to inhibit MAO (monoamine oxidase) enzyme, thus producing antidepressive effects. 1,2 Nicotine patches can improve the mood in depressed patients. 3 However, it is unclear, if nicotine or other chemicals directly affect the brain of a depressed person.…”
Section: Introductionmentioning
confidence: 99%